THE INFLUENCE OF A GUIDED INQUIRY LEARNING MODEL ON STUDENT MOTIVATION AND LEARNING OUTCOMES ON SOLAR SYSTEM MATERIAL - Simamora, Nadia Natalia; Kimball, Derek F. Jackson; Maulana, Rizki Catur Dimas; Sunarmi, Nani (EduFisika: Jurnal Pendidikan Fisika, 2024)
This research aims to determine the effect of the guided inquiry learning model on student motivation and learning outcomes at Junior high school 2 Piyungan. This research uses a quantitative approach with a quasi-experimental type of research in the form of Nonequivalent Control Group Design. The population of this study were all students in class VII of Junior high school 2 Piyungan with a sample of 64 students. The research instruments used were test instruments in the form of multiple choice questions and non-test instruments in the form of questionnaires. The data analysis technique used in the research is descriptive statistical analysis and inferential data analysis using the Paired Sample t-test and MANOVA test. The research results were analyzed using statistical analysis showing that the average value of learning motivation and learning outcomes for experimental class students was greater than that of the control class. These results are supported by the results of inferential analysis using the MANOVA test which shows a sig. (2-tailed) 0.000 < 0.05. This means that H0 is rejected and Ha is accepted. Thus, it can be said that the guided inquiry learning model influences student motivation and learning outcomes. This research can be used as a reference for further research regarding the influence of the guided inquiry learning model on student motivation and learning outcomes.